2013
DOI: 10.1007/s10875-013-9915-0
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies to Variable Heavy (VH) Chain Ig Sequences in Humans Impact the Safety and Clinical Pharmacology of a VH Domain Antibody Antagonist of TNF-α Receptor 1

Abstract: Our data support a greater focus on the impact of pre-existing, drug-reactive autoantibodies on the development of antibody fragments and biotherapeutics targeting cell surface receptors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
70
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 30 publications
4
70
0
Order By: Relevance
“…toxins, viral proteins, and cytokines (13)(14)(15)(16)(17)(18). Naturally occurring antibodies to neoepitopes that are revealed after conformational change of a biotherapeutic with reactivity to the hinge region and/or other internal residues of the IgG have also been reported (19)(20)(21).…”
Section: Classification (Definition) Of Pre-existing Drug-reactive Anmentioning
confidence: 99%
See 1 more Smart Citation
“…toxins, viral proteins, and cytokines (13)(14)(15)(16)(17)(18). Naturally occurring antibodies to neoepitopes that are revealed after conformational change of a biotherapeutic with reactivity to the hinge region and/or other internal residues of the IgG have also been reported (19)(20)(21).…”
Section: Classification (Definition) Of Pre-existing Drug-reactive Anmentioning
confidence: 99%
“…Pre-existing antibodies that recognize the idiotopes are expected to interfere with target binding when the idiotopes are part of the antigen binding site, or in close proximity to the antigen binding site. These antibodies may lead to drug neutralization, loss of efficacy, and ultimately treatment failure (20,34). Pre-existing antibodies recognizing the allotopes of antibody biotherapeutics are less likely to neutralize the interaction between the biotherapeutic and the target, therefore, less likely to cause rapid clearance of the drug or have major impact on efficacy (35).…”
Section: Pre-existing Antibodies To Antibody-based Biotherapeuticsmentioning
confidence: 99%
“…Another example of pre-existing antibodies to an antibody fragment comes from a study by Holland et al 29 About 50% of healthy individuals were found to have antibodies against a single VH domain antibody fragment that targets TNFR-1. In a doseescalation study, physiological signs of cytokine release were observed in 2 individuals with anti-VH antibodies, and, in an in vitro experiment, complexes of anti-VH antibodies and the anti-TNFR-1 VH domain antibody were able to release cytokines from several human cell lines.…”
Section: Anti-hinge Antibodies and Other Antibodies To Igg Fragmentsmentioning
confidence: 99%
“…108,109 Another example is the use of single-chain VH domains, of which one example was discussed above. 29 Whether or not these modifications will lead to substantial antibody formation remains to be seen. Furthermore, a variety of antibody conjugates are in development, such as molecules comprising toxins coupled to an antibody.…”
Section: Immunogenicity Assaysmentioning
confidence: 99%
“…Although the prevalence of these autoantibodies was high (74%), thrombocytopenia was seen in only 1-2% of patients. Pre-Abs to an anti-TNFR1 heavy chain domain antibody fragment were found in approximately 50% of drug naïve healthy human subjects (53). These antibodies did not cross-react with larger antibody fragments or full mAb, suggesting that, as in the case of anti-hinge autoantibodies, they recognized a cryptic epitope exposed after the cleavage.…”
Section: Monoclonal Antibodies and Antibody Fragmentsmentioning
confidence: 95%